Kazakh-Turkish partnership in our time: key trends and main challenges (International relations and international law Journal, 2016)
This article mainly deals partnership between Kazakhstan and Turkey, describes the important directions ofdevelopment and its main objectives that exist in our time between the two countries. Turkey today is an essential and trusted partner of Kazakhstan in the Eurasian continent. In this regard, the article mainly analyzes the degree of development of these relations and the prospect of rapidly developing sectors of the Kazakh-Turkish relations. And also focuses on the development of bilateral investment. At the end of the article predicted the future of the Kazakh-Turkish partnership and noted that historical, common cultural and spiritual values of these relationships will remain the basis for development of partnership betweenthe two countries.
Keywords: economic; policy; рartner; investment; strategy